2019
DOI: 10.1038/s41598-019-48943-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of stem endophytic communities revealed developmental stage as one of the drivers of fungal endophytic community assemblages in two Amazonian hardwood genera

Abstract: Many aspects of the dynamics of tropical fungal endophyte communities are poorly known, including the influence of host taxonomy, host life stage, host defence, and host geographical distance on community assembly and composition. Recent fungal endophyte research has focused on Hevea brasiliensis due to its global importance as the main source of natural rubber. However, almost no data exist on the fungal community harboured within other Hevea species or its sister… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 71 publications
(69 reference statements)
3
18
0
Order By: Relevance
“…In total, only 18 filamentous, ascomycetous endophytes (8 -10 species per seedling) were isolated in this study, whereas 103 different species (5 -22 isolated per tree) were found in mature pine shoots in a study by Bußkamp et al (2020). Foliar fungal endophyte assemblages have been shown to vary between the developmental stage of the host (mature vs. seedling (Helander et al, 2011;Koukol et al, 2012;Skaltsas et al, 2019). The core foliar endophytes seem to be the same in seedlings and mature Scots pine (Blumenstein et al, 2020;Bußkamp et al, 2020) but community compositions and species differences are probably related to the age of the host (Taudière et al, 2018).…”
Section: Pre-colonization Of the Trees With Fungal Communitymentioning
confidence: 67%
“…In total, only 18 filamentous, ascomycetous endophytes (8 -10 species per seedling) were isolated in this study, whereas 103 different species (5 -22 isolated per tree) were found in mature pine shoots in a study by Bußkamp et al (2020). Foliar fungal endophyte assemblages have been shown to vary between the developmental stage of the host (mature vs. seedling (Helander et al, 2011;Koukol et al, 2012;Skaltsas et al, 2019). The core foliar endophytes seem to be the same in seedlings and mature Scots pine (Blumenstein et al, 2020;Bußkamp et al, 2020) but community compositions and species differences are probably related to the age of the host (Taudière et al, 2018).…”
Section: Pre-colonization Of the Trees With Fungal Communitymentioning
confidence: 67%
“…plants also, microbiome is reported to have significant variation based on different geographical locations, such as reported in the case of vineyards, Amazonian hardwood, and fragrant orchid. The researchers co-relate the variations in the plant microbiome to various factors such as location/genetics/abiotic and biotic factors (Coller et al, 2019;Skaltsas et al, 2019;Lin et al, 2020). However, reports are emerging on the core microbiome that remains unaltered at various developmental stages of the plants or plants from different locations/niches (Chen et al, 2018;Toju et al, 2018;Lin et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The previous study revealed that the root-associated microbiomes has been proven to be associated with the plant developmental stages (Lundberg et al, 2012;Skaltsas et al, 2019). To investigate the relationship between growth stage and the root-associated microbiome, two growth stages in two different growing regions were tested and compared.…”
Section: Comparative Analyses Of Core Microbiome Across Plant Growth mentioning
confidence: 99%